Atomic Layer Deposition of Ultrathin TaN and Ternary Ta1-XAlXNy Films for Cu Diffusion Barrier Applications in Advanced Interconnects. (10th September 2015) - Consiglio, Steven; Yu, Kyle; Dey, Sonal; Tapily, Kandabara; Clark, Robert D.; Hasegawa, Toshio; Wajda, Cory S.; Leusink, Gert J.; Diebold, Alain C.
Abstract : Ultrathin TaN and Ta1-x Alx Ny films were deposited by ALD using metallorganic precursors and were evaluated for their effectiveness in Cu diffusion barrier applications compared to a PVD TaN control. Ta1-x Alx Ny films with x = 0.21-0.88 were deposited by varying Ta:Al cycle ratios. The effectiveness of the barrier layers against Cu diffusion was investigated using in-situ-ramp-anneal-synchrotron-XRD on stacks with 1.8 nm layers between 50 nm PVD Cu and Si. The kinetics of Cu3 Si formation was assessed by performing a Kissinger-like analysis to determine the effective activation energy (Ea ) for Cu silicidation. Compared to the stack with a PVD TaN barrier, the stacks with the ALD films exhibited a higher crystallization temperature for Cu silicidation. Based on the estimated Ea values, grain boundary and lattice diffusion of Cu were identified as the dominant failure mechanisms for the ALD and PVD films, respectively. For 3 nm films, GIIXRD showed evidence of nanocrystallites embedded in an amorphous matrix with broad peaks corresponding to cubic phase for the ALD films and hexagonal phase for the PVD film. The superior performance of the ALD barriers has been attributed to the formation of a higher density cubic phase in the ALD films as compared to the lower density hexagonal phase in the PVD film. The study further elucidates the difference in initial failure mechanisms due to differences in barrier crystallinity and associated phase. Additionally, incorporation of Al in ALD Ta1-x Alx Ny (x=0.33) seems to aid the formation of a barrier film which is closer to amorphous than the case of ALD TaN.